Sistem Pendukung Keputusan Pemberian Bonus Sales Menggunakan Metode TOPSIS - Wahyudin, W; Handayani, Popon; Syahriani, S (STIKOM Tunas Bangsa Pematangsiantar, 2021)
In improving the quality of employee performance in a company, it is necessary to have motivation in the form of giving employee bonuses. Bonuses are additional wages given to employees for the achievement of the best work they have done. PT Lexus Elektronik itself has implemented bonuses for its employees, it's just that the bonuses are given based on sales achievement targets and have not used an assessment based on other supporting criteria. This research was made in order to assist company leaders in determining employee bonuses, especially in the Sales section by taking into account several objective criteria. The method used in this research is the TOPSIS (Technique For Others Preference by Similarity To Ideal Solution) method with several assessment criteria, namely sales, service, performance, teamwork and attendance. The TOPSIS method has several stages, namely: determining the normalization of the decision matrix, determining the normalized weight of the matrix, the distance between the alternative Ai and the ideal positive solution, the distance between the alternative Ai and the negative ideal solution, the preference value for each alternative (Vi). After the calculation process of these stages is carried out, the highest preference result is 0.697 (V14)